The devil's ransom [compact disc, unabridged] - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2023)
Pike Logan must race to stop an insidious attack orchestrated by a turncoat who cloaks his attacks behind hackers from Serbia and Russia, and who knows America's most treasured secrets.